Warehouse management model integrating 5S methodology and ABC classification to optimize space utilization and search time in a commercial SME - Diaz Callo, Andrea A. (2024)
Currently, large quantity of Peruvian SMEs does not count with the resources and tools to establish an adequate warehouse management. This problem results in high costs of keeping items in the warehouse, inefficient utilization of space and poor visibility of products within the warehouse. For that reason, the objective of this study is to present an accessible model than can be implemented in SMEs of the wholesale sector that are interested in improving their warehouse practices. Therefore, the contribution of this article is based on the design of a warehouse management model, that allows the areas on the warehouse to be organize and stablish a correct way of product placement. The model is composed by two classic tools for inventory and warehouse management, the 5s methodology and the ABC method. The obtained results demonstrate that it is possible to reduce searching times from 216.75 min to 148.75 min; to establish order and organization within the warehouse, with an improvement of 47% in the 5s level; to maintain the utilization at percentages greater than 95%, and reduced the space occupied by waste to 0.